Enhancing Destination Competitiveness: A Thematic Approach to Nature-Based Tourism in Sikka Regency, East Nusa Tenggara Province - Desiderius Siga Meli Poa (Cita konsultindo, 2025)
This study aims to identify exisiting condition of nature-based tourism, community participation and formulate strategic directions for its future development. A qualitative approach was adopted, involving in-depth interviews with key stakeholders, including tourism industry representatives, local communities, and academics. The findings highlight two primary themes in nature-based tourism development, namely: terrestrial and marine tourism. However, the integration and implementation of these themes remain inadequate, leading to limited destination competitiveness. Moreover, the community participation in creating nature based tourism product is still low as well. To address this issue, this study proposes a theoretical model for enhancing the development of nature-based tourism. The novelty of this research lies in the strategic positioning of core and supporting themes within the product positioning framework, enhancing the region’s competitive edge in the nature tourism sector.